Mineralogical analysis by X-Ray diffraction of Hashilan Wetland sediment core, western Iran - Reza Safaierad; Christoph Vogt (PANGAEA, 2023)
For mineralogical analysis by X-Ray Diffraction (XRD), samples of ~ 1 gram were dried at 50 °C for 48 hours. The dried samples were ground and homogenized using mortar and pestle. XRD analyses were carried out at the Crystallography and Geomaterials Group, Dept. of Geosciences, University of Bremen. The X-ray diffractograms have been measured on a Philips X extquotesinglePert Pro multipurpose diffractometer equipped with a Cu-tube (kα 1.541, 45 kV, 40 mA), a fixed divergence slit of extonequarter°, a 16 samples changer, a secondary Ni-Filter, and the X extquotesingleCelerator detector system. Measurements were performed as a continuous scan from 3–65° 2 exttheta, with a calculated step size of 0.016° 2 exttheta (calculated time per step was 100 s). Minerals were identified with the Philips/Panalytical software X extquotesinglePert HighScore™, which can also give a semi-quantitative value for each identified mineral on the basis of Relative Intensity Ratio (R.I.R)-values. The R.I.R.-values are calculated as the ratio between the intensity of the most intense reflex of a specific mineral phase and the intensity of the most intense reflex of pure corundum (I/Ic) referring to as the "matrix-flushing method" after Chung (1974).
In: Safaierad, Reza; Zolitschka, Bernd; Djamali, Morteza; Dupont, Lydie M; Vogt, Christoph; Matthews, Roger (2023): Pollen, grain size, loss-on-ignition, elemental and mineralogical composition, magnetic susceptibility and radiocarbon measurements in Hashilan Wetland sediment core [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.956292